Ethanol-Induced Leakage in Saccharomyces cerevisiae: Kinetics and Relationship to Yeast Ethanol Tolerance and Alcohol Fermentation Productivity - Salgueiro, Sancha P. (1988)
Ethanol stimulated the leakage of amino acids and 260-nm-light-absorbing compounds from cells of Saccharomyces cerevisiae. The efflux followed first-order kinetics over an initial period. In the presence of lethal concentrations of ethanol, the efflux rates at 30 and 36°C were an exponential function of ethanol concentration: k(e)(X) = k(e)(Xm)e(E (X-X(m))), where k(e)(X) and k(e)(Xm) are the efflux rate constants, respectively, in the presence of a concentration X of ethanol or the minimal concentration of ethanol, X(m), above which the equation was applicable, coincident with the minimal lethal concentration of ethanol. E is the enhancement constant. At 36°C, as compared with the corresponding values at 30°C, the efflux rates were higher and the minimal concentration of ethanol (X(m)) was lower. The exponential constants for the enhancement of the rate of leakage (E) had similar values at 30 or 36°C and were of the same order of magnitude as the corresponding exponential constants for ethanol-induced death. Under isothermic conditions (30°C) and up to 22% (vol/vol) ethanol, the resistance to ethanol-induced leakage of 260-nm-light-absorbing compounds was found to be closely related with the ethanol tolerance of three strains of yeasts, Kluyveromyces marxianus, Saccharomyces cerevisiae, and Saccharomyces bayanus. The resistance to ethanol-induced leakage indicates the possible adoption of the present method for the rapid screening of ethanol-tolerant strains. The addition to a fermentation medium of the intracellular material obtained by ethanol permeabilization of yeast cells led to improvements in alcohol fermentation by S. cerevisiae and S. bayanus. The action of the intracellular material, by improving yeast ethanol tolerance, and the advantages of partially recycling the fermented medium after distillation were discussed.